Methods and materials for eliminating nematode pests in black pepper - Wong, Sing King; Pau, Chen Guan; Leong, Stephen Chan Guan; Ahmed, Osumanu Haruna (2013)
The present invention pertains to the use of the fungi Paecilomyces lilacinus (Thom) Samson in the protection of the roots of the black pepper plant from nematode infestations. The invention surprisingly found the applicability of the fungus as biological pest control agent for black pepper plant cultures. The invention disclosed provides methods of using Paecilomyces lilacinus (Thom) Samson as well as two indigenous strains of Paecilomyces lilacinus that were isolated and characterized, and that proofed useful against the root-knot nematode.